Encounters with Chinese writers - Dillard, Annie (Wesleyan University Press ; Distributed by Harper & Row, 1984)
Bizarre encounters between Chinese and American writers.
Keywords: Authors, Chinese -- 20th century -- Anecdotes.; Écrivains chinois -- 20e siècle -- Anecdotes.; LITERARY CRITICISM -- Asian -- General.; Authors, Chinese; Schriftsteller; Erlebnisbericht; China; 1900-1999; Anecdotes